MEDB-70. Metabolism mediated radiation resistance in MYC-driven Medulloblastoma. (3rd June 2022) - Veo, Bethany; Goodspeed, Andrew; Prince, Eric; Venkataraman, Sujatha; Vibhakar, Rajeev
Abstract: Medulloblastoma (MB) is the most prevalent malignant brain tumor in children and demonstrates a high level of heterogeneity. Treatment for MB includes chemotherapy and radiation often resulting in long-term morbidity. MYC-driven MB, are high-risk tumors with poor long-term survival and increased susceptibility to develop recurrent tumors. Recurrent MB is far more aggressive with limited treatment options leading to a 5-year survival rate of 12%. To understand what drives MYC-amplified MB relapse we performed single-cell RNA sequencing of irradiated MB xenograft tumors. We identified an overall enhancement of metabolic activity in radiation-resistant cells. We further observe enhanced wild-type IDH1 and IDH2 expression in two clusters, which coincide with hypoxia and Nestin expression, marking a stem-cell like niche. Stem-like cancer cells are notoriously resilient against radiation therapy. Furthermore, wtIDH1 and IDH2 represent a unique target in radiation-resistant MB which has not previously been identified. Wild type IDH1/IDH2 are more recently shown to promote tumor proliferation and mediate metabolic reprogramming through the production of oncometabolites and substrates that functionally alter chromatin structure and gene transcription. We hypothesized that MYC modulation of wtIDH1/IDH2 facilitates metabolic reprogramming and promotes radiation-resistant cell populations. We show the change in the structural integrity of chromatin altered in radiation-resistant MB by metabolic adaptation and the effect of disrupting IDH1/IDH2 activity. We further compare these results to the chromatin profile of patient primary and matched relapsed MB samples at the single-cell level. We demonstrate that targeting IDH1/2 with chemical inhibitors suppresses MB cell growth. Our results disclose insights into the development of radiation resistance and provide a potential therapeutic target for the treatment of relapsed MYC-MB.